Design of a brushed DC motors PID controller for development of low-cost robotic applications (2014)
This article present the design and construction of a PID controller for direct current motors motion control in low-cost robotic applications. The reasons which led us to the make the proposal and design of the system were, on the one hand, the need for robotic developments by students in Colombians academic environments with the resources available locally, and on the other hand, the need for a teaching of the robotics based on laboratory practices of the most commonly used control algorisms in this area, such as: the inverse kinematics based PID control and the dynamic control by calculated torque. © 2014 IEEE.